Modeling free-radical polymerizations with depropagation using Java(TM): Methyl methacrylate/alpha-methylstyrene at elevated temperatures. - Badeen, Christopher. (University of Ottawa (Canada), 2000)
There is growing interest in polymerization reactions at elevated temperatures due to potential advantages of elevated-temperature operation. However, most studies to date have focused on polymerization reactions at relatively low temperatures (i.e., below 80°C). This study of the copolymerization of methyl methacrylate (MMA) and alpha-methylstyrene (alpha-ms) at elevated temperatures (100--140°C), is in response to both the growing interest in the area of elevated temperature polymerization and the scarcity of knowledge in this area. A computer program was written in the Java(TM) programming, language to simulate the copolymerization being investigated. This is the first published use of Java(TM) to write a numerical polymerization simulation program. The program implements the model for free-radical polymerization described in Dube et al. (1997), but with modifications to account for reverse polymerization reactions. The model described by Kruger (1987) was used to account for reversible polymerization reactions. The results of this investigation indicate that the model used for this system shows promise. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.